IMPLEMENTASI PROGRAM KKN MEMBACA UNTUK MENINGKATKAN KEMAMPUAN LITERASI SISWA KELAS II MELALUI POJOK LITERASI UPT SDN NO. 78 BALANG, DESA BONTOKASSI, KABUPATEN TAKALAR - Nurul Ibrahim; Sitti Astriani Nurkhadijah; Ratnawati; Ika Zulfika (Almeera Education, 2026)
The Community Service Program for Education (KKN-Dik) of Muhammadiyah University of Makassar was implemented as a form of community engagement and practical application of educational theories. One of the main activities was the implementation of a Literacy Corner at UPT SDN No.78 Balang, Bontokassi Village, Takalar Regency. This program aimed to improve the reading interest and literacy skills of second-grade students through reading activities conducted both in the library and in the classroom. The research employed a descriptive qualitative approach, involving planning, implementation, and observation of students’ reading activities. The results indicated an increase in students’ reading interest and comprehension skills. Students who were initially passive and less motivated to read became more focused and enthusiastic when participating in literacy corner activities. Moreover, positive behavioral changes were observed, such as improved independence in reading and writing. Therefore, the implementation of the literacy corner proved to be effective in fostering an early culture of literacy in the elementary school environment.